Metal health of mothers of children with autism spectrum disorder - Blumberg, Chevon (My University, 2015)
Autism Spectrum Disorder (ASD) may have an impact on maternal mental health. Maternal mental health may also be influenced by the socio-economic variables of single parenthood, and lack of income. AIM OF STUDY: The aim of the study was to compare the mental health of mothers of children with ASD, with a control group. The total group was divided using the socio-economic variables of single parenthood and lack of income in order to compare the impact of these variables on maternal mental health. DESIGN, SETTING AND PARTICIPANTS: A cross-sectional study design was used for descriptive and comparative purposes. Data was collected from mothers of children with either ASD or asthma, who functioned as the control group, who were patients at a hospital in Johannesburg, South Africa. METHODS: 101 mothers of children who were patients at the hospital were assessed. Participants were administered a demographic data questionnaire, and a standardised questionnaire for assessing symptoms of depression, anxiety and stress (Depression, Anxiety, Stress Scale- DASS). RESULTS: There was no significant difference between the two groups of mothers on socio-economic variables (p>0.05), with the exception of government grant receipt (p=0.01). Although there was a trend for higher scores in the ASD group, this study found no significant difference in the mental health status of mothers of children with ASD when compared to the control group. Similarly, no significant difference was found in the mental health status between mothers who were in a relationship, when compared to mothers who were not in a relationship (p>0.05). A significant difference was found between mothers who received an income and those who did not, on all three subscales of depression, anxiety and stress (p<0.05). These differences were more pronounced in the ASD group, with these mothers scoring consistently higher than the control group. CONCLUSION: ASD was not shown to have a significant impact on maternal mental health, when compared to a control group. Single mothers were not shown to experience significantly more psychological distress than those mothers who were in a relationship. Lack of income was shown to significantly increase the symptoms of depression, anxiety and stress in mothers participating in this study. This impact was more pronounced in those mothers who had children living with ASD.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in Child Health (Neurodevelopment) Johannesburg, 2015